The evolution of Darwinism: Selection, adaptation, and progress in evolutionary biology - Shanahan, Timothy (Cambridge University, 2013)
Alas, the apparent simplicity of Darwin's theory is deceptive. From the very beginning it has been subject to differing interpretations, and even now professional opinion is sharply divided on a range of fundamental issues, among them the nature of selection, the scope of adaptation, and the question of evolutionary progress. This book traces these issues from Darwin's own evolving quest for understanding to ongoing contemporary debates, and explores their implications for the greatest questions of all: where we came from, who we are, and where we might be heading." "Written in a clear and nontechnical style, this book will be of interest to students, scholars, and anyone wishing to understand the development of evolutionary theory.